The development of arc welding apparatus: As indicated by the oscillograph - Holslag, C. J. (Journal of the A.I.E.E., 1930)
THE development of arc welding apparatus to its present efficient form has been a gradual process of evolution. In the early days all that was thought necessary for arc welding was a source of power which would supply the proper amperage; the ordinary 110-volt line, transformer, or d-c. generator, were considered entirely adequate. These sources of power were used in connection with a resistance or reactance to control the current to the desired value; in fact, at that time the proper amperage was not definitely known. In general it might be stated that the values of current used, particularly for heavier material, was entirely too low.